New insights into diabetes burnout and its distinction from diabetes distress and depressive symptoms: A qualitative study. (November 2020) - Abdoli, Samereh; Hessler, Danielle; Smither, Betsy; Miller-Bains, Katherine; Burr, Erin M.; Stuckey, Heather L.
Abstract: Aims: This study aimed to corroborate the main hypotetized dimensions of diabetes burnout, and its distinction from diabetes distress and depressive symptoms among adults with type 1 diabetes (T1D). Methods: A qualitative descriptive study was employed to collect data from 31 eligible participants using semi-structured individual phone interviews. Participants were recruited through purposive sampling among a larger sample of adults with T1D in a previous study. Data was analyzed using qualitative content analysis including immersion, reduction, and interpretation. Results: Exhaustion and detachment were frequent manifestations of diabetes burnout that often accompanied by instances during which participants experienced a loss of control over diabetes. Whereas individuals' support systems could either help or hinder diabetes burnout. Participants saw burnout as separate but closely related to distress and depressive symptoms, with some suggesting correlations among burnout, distress, and depressive symptoms, while others expressed that distress caused their burnout and depressive symptoms. Conclusions: Diabetes burnout reflects a significant yet unexplored concept which might explain the complexities of suboptimal self-management and poor diabetes outcomes. Emerging evidence suggesting diabetes burnout as a distinct concept calls for more studies to mitigate diabetes burnout as an obstacle to optimal diabetes care.